Unveiling a Key Intermediate in Solvent Vapor Postannealing to Enlarge Crystalline Domains of Organometal Halide Perovskite Films. (10th February 2017) - Xiao, Shuang; Bai, Yang; Meng, Xiangyue; Zhang, Teng; Chen, Haining; Zheng, Xiaoli; Hu, Chen; Qu, Yongquan; Yang, Shihe
Abstract : Hybrid organic/inorganic perovskite solar cells (PSCs) have shown great potential in meeting the future challenges in energy and environment. Solvent‐vapor‐assisted posttreatment strategies are developed to improve the perovskite film quality for achieving higher efficiency. However, the intrinsic working mechanisms of these strategies have not been well understood yet. This study identifies an MA2 Pb3 I8 (DMSO)2 intermediate phase formed during the annealing process of methylammonium lead triiodide in dimethyl sulfoxide (DMSO) atmosphere and located the reaction sites at perovskite grain boundaries by observing and rationalizing the growth of nanorods of the intermediate. This enables us to propose and validate an intermediate‐assisted grain‐coarsening model, which highlights the activation energy reduction for grain boundary migration. Leveraging this mechanism, this study uses MABr/DMSO mixed vapor to further enhance grain boundary migration kinetics and successfully obtain even larger grains, leading to an impressive improvement in power conversion efficiency (17.64%) relative to the pristine PSCs (15.13%). The revelation of grain boundary migration‐assisted grain growth provides a guide for the future development of polycrystalline perovskite thin‐film solar cells. Abstract : MA2 Pb3 I8 (DMSO)2 intermediate is identified and tracked during the methylammonium lead triiodide thin‐film anneal process under dimethyl sulfoxide (DMSO) solvent vapor, which helps to reduce the activation energy of perovskite grain boundary migration. Leveraging this mechanism, an MABr/DMSO mix vapor anneal method is developed to further facillitate grain goundary migration to achieve 17.64% efficiency in NiO‐based inverted perovskite solar cell.